RANCANG BANGUN MICRO AIR VEHICLE KONFIGURASI TAILLESS - Taufiq Mulyanto; Arinta H Wijaya; Hari Muhammad (Mesin, 2008)
Nowadays, Micro Air Vehicle (MAV) is mostly developed for surveillance purpose, either for military or civilian. In this article, a design and building of a MAV will be presented. A tailless configuration was chosen. The design and build process started with a study of several design parameters of existing MAVs. Then, it is followed by initial sizing, detail design and production of the MAV. In general, the designed MAV could meet the design requirements and objectives stated. Some preliminary tests had shown that the basic flying characteristics was sufficiently good, although further development still has to be done. The design and build process was also able to evaluate the implementation of some aircraft design formula and method being implemented to design MAV.